The Behavior of Spanish Conquerors and Colonizers in America Is a Root Cause of Political Instability in Argentina - Felice, Carmelo José; Ruiz, Gabriel Alfredo (Journal of Advanced Research in Social Sciences, 2025)
The political stability of Argentina is a striking phenomenon in the scientific realm. This work factually demonstrates that one of the origins of instability is the contempt of the Spanish in America for the authority of the Spanish Crown, a behavior born during the stage of conquest and colonization of America. The validation process consists of a historical analysis that is summarized in propositionally logical statements, which allow the deduction and confirmation of the initial hypothesis. For the demonstration, violations of Royal edicts are analyzed, including the prohibition of slave labor and the obligations to only buy products from Spain, to treat the indigenous people well, and to consider them free men with rights to their territories. In all cases, the violations did not have significant punishments, probably due to the practical impossibility of controlling offenders from a distance, in a historical context where efficient means of communication did not exist. This lack of punishment gave rise to a contempt for authority, a custom that was passed down from generation to generation and is currently manifested as the contempt of all citizens for laws and regulations issued by any authority. This behavior partially explains the current political instability in Argentina.